Case report: IL12RB1 deficiency in an infant with disseminated Bacille Calmette-Guérin disease - Ma, Xiao; Chen, Juping; Cheng, Junqiao; Wang, Jingbo (Frontiers in Immunology, 2026)
Disseminated Bacille Calmette-Guérin (BCG) disease is a rare adverse reaction to BCG vaccination. We report a neonate presenting with a progressive left axillary mass 3 months post-vaccination. High-throughput sequencing confirmed Mycobacterium bovis (BCG strain) infection. Genetic testing confirmed inborn errors of immunity (IEI) caused by interleukin (IL) 12 receptor β1 deficiency. An expert panel diagnosed BCG disease (acute hematogenous disseminated BCG disease and axillary lymph node involvement) due to the immunodeficiency. After about 28 months of anti-BCG combination therapy with interferon-gamma (IFN-γ), the infection was successfully controlled. The patient continues to receive maintenance therapy with only interferon-gamma (IFN-γ). The study explores the optimal timing and target populations for BCG vaccination in high TB burden countries to minimize severe adverse effects.